ANALISIS MISKONSEPSI SISWA KELAS VIIB SMP NEGERI 12 JEMBER DENGAN MENGGUNAKAN METODE THREE TIRE TEST PADA MATERI ALJABAR - Wahyuni, Indah; Hanum, Malika; Firnanda, Dwi Tri Fresti; Anam, Khoirul (INSPIRAMATIKA, 2023)
This research aims to determine the misconceptions of class VII B students at SMPN 12 Jember using a qualitative descriptive. Instrument method used by researchers in the form of written test questions on algebra material consisting of three items with the Three Tier Test method which has three levels of difficulty, namely low, medium and high. The Three Tier Test method questions have three levels of questions, namely questions for understanding students' concepts, questions about the reasons for students' answers, and finally questions about students' confidence in answering these questions. From the research that has been carried out, several misconceptions have emerged, namely, the misconception of solving algebra is 61.2% of the total number of questions, the misconception of algebraic operations is 58.1% of the total number of questions, and the misconception of sign errors is 87.1% of the total number of questions.